(untitled) (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2018)
The primary aim of this paper is to present the main lexical, stylistic, morphological and syntactic characteristics of the language used in football match reports of the media in Spanish. Due to the fact that football is the sport with the most followers around the world, in recent years we have witnessed the increase of consumption of relevant texts, especially with the emergence of the specialized media on the Internet. The paper first addresses the issue of defining the genre of la crónica futbolística and its formal aspects, and then we proceed with the presentation of the most prominent linguistic features. Being a specialized genre, it is based on a specific terminology, so we further present the main characteristics of some of the terms from the morphological, lexical and phraseological points of view, based on recent corpus research. Finally, some relevant syntactic phenomena of the genre are mentioned, with emphasis on the most frequent deviations from the standard norm, as it’s demonstrated in the literature. Additionally, the secondary aim of this article is to present the findings of some exhaustive new studies that address different aspects of football slang, as we are convinced that they can be very useful as a basis for future empirical research. In conclusion, it is evident that the texts on football in general and especially the field of football slang are extremely suitable for any type of linguistic research. The prolific production of media texts helps establishing a broader authentic corpus, and thus facilitates any study of the real language use in this specific domain. Key words: specific language, style, terminology, match report, football.